Uncovering the Hidden Physical Structures and Protostellar Activities in the Low-metallicity S284-RE Region: Results from ALMA and JWST - O. R. Jadhav; L. K. Dewangan; Aayushi Verma; N. K. Bhadari; A. K. Maity; Saurabh Sharma; Mamta (The Astrophysical Journal)
We present an observational study of the S284-RE region, a low-metallicity area associated with the extended S284 H ii region. A thermally supercritical filament (mass ∼2402 M _⊙ and length ∼8.5 pc) is investigated using the Herschel column density map. The Spitzer ratio 4.5 μ m/3.6 μ m map traces the H _2 outflows in this filament, where previously reported young stellar objects (YSOs) are spatially distributed. Analysis of the YSO distribution has revealed three active star-forming clusters (YCl1, YCl2, and YCl3) within the filament. YCl3 seems to be the most evolved and YCl2 the youngest, while YCl1 displays signs of nonthermal fragmentation. The JWST (F470N+F444W)/F356W ratio map reveals at least seven bipolar H _2 outflows, with four (olc1–olc4) in YCl1 and three (ol1–ol3) in YCl2. The driving sources of these outflows are identified based on outflow geometry, Atacama Large Millimeter/submillimeter Array (ALMA) continuum peaks, and YSO positions. Two ALMA continuum sources—#2 and #3—from the M – R _eff plot are recognized as potential massive star formation candidates. ALMA continuum source #2 hosts at least three outflow-driving sources, whereas ALMA continuum source #3 contains two. The bipolar outflow olc1, driven by an embedded object within continuum source #2, is likely a massive protostar, as indicated by the Br- α and PAH emissions depicted in the JWST (F405N+F444W)/F356W ratio map. The presence of H _2 knots in the outflows olc1 and ol1 suggests episodic accretion. Overall, the study investigates a massive protostar candidate, driving the ∼2.7 pc H _2 outflow olc1 and undergoing episodic accretion.